The biting and predaceous midges of Guadeloupe (Diptera: Ceratopogonidae) I. Species of the subfamily Ceratopogoninae - Grogan, William L. (2013)
We provide new records of biting and predaceous midges (Diptera: Ceratopogonidae) from Guadeloupe in the subfamily Ceratopogoninae, including descriptions and illustrations of three new predaceous species in the genera, Parabezzia Malloch, Stilobezzia Kieffer and Palpomyia Meigen, respectively, and the first records of the New World predaceous genus, Amerohelea Grogan and Wirth, from the Caribbean region. We also provide the first Guadeloupe records of the biting midges, Culicoides (Anilomyia) decor (Williston), C. (Avaritia) pusillus Lutz, C. (Drymodesmyia) bredini Wirth and Blanton, C. (D.) poikilonotus Macfie, C. (Haematomyidium) hoffmani Fox, C. (Hoffmania) insignis Lutz, C. rangeli Ortiz and Mirsa and C. trilineatus Fox, and the predaceous midges, Brachypogon (Brachypogon) bifidus Spinelli and Grogan, B. (B.) telesfordi Spinelli and Grogan, B. (B.) woodruffi Spinelli and Grogan, Monohelea maya Felippe-Bauer, Huerta and Ibáñez-Bernal, Stilobezzia (Stilobezzia) diminuta Lane and Forattini, S. (S.) thomsenae Wirth, Amerohelea galindoi Grogan and Wirth, Bezzia (Bezzia) flinti Spinelli and Wirth, B. (Homobezzia) venustula (Williston) and Palpomyia insularis Spinelli and Grogan.